Determinants Influencing the Readiness of Non-Medical Hospital Personnel to Perform Basic Life Support - Elin Hidayat; Suaib Suaib; I Made Rio Dwijayanto; Nur Aviva Pemasi; Ilne Ai Purana Adel (Jurnal Keperawatan Indonesia)
All healthcare personnel, including both medical and non-medical staff within hospitals, are expected to possess the capability to administer Basic Life Support (BLS) in order to provide immediate assistance during emergencies. However, many non-medical hospital staff remain unprepared to perform BLS due to a lack of knowledge, willingness, and confidence. This study aims to identify the factors affecting the preparedness of non-medical hospital staff in carrying out BLS at Undata Hospital, a healthcare facility in Central Sulawesi. This research employed quantitative design with a cross-sectional approach. The sample comprised 103 non-medical respondents selected through total sampling. Data were collected through structured interviews and self-administered questionnaires. The variables measured in this study include behavioral beliefs, normative beliefs, control beliefs, intention, and BLS readiness. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that behavioral beliefs significantly influenced intention (p = 0.040), while normative beliefs did not (p = 0.128). Control beliefs showed no significant influence on intention (p = 0.058), whereas intention had a significant effect on BLS readiness (p = 0.046). The study concludes that behavioral beliefs influence intention, which in turn significantly affects BLS readiness.